The mediating effects of resilience in the relationship between social support and posttraumatic growth in patients with acute coronary syndrome in China - Tang, Nan; Masingboon, Khemaradee; Hengudomsub, Pornpat (Belitung Raya Foundation, Indonesia, 2024)
Background: Posttraumatic growth has a positive impact on patients diagnosed with acute coronary syndrome (ACS). Patients with acute coronary syndrome in China report low to moderate levels of posttraumatic growth. Additionally, there is a dearth of research exploring the associations between resilience, social support, and posttraumatic growth in this specific patient population. Objective: This study examined whether resilience serves as a mediator between social support and posttraumatic growth in patients with acute coronary syndrome who had been discharged for 1 to 6 months and were being followed up in clinics. Methods: A descriptive correlational study design was utilized. A systematic sampling technique was used to recruit 121 patients with acute coronary syndrome who had been discharged for 1 to 6 months from cardiovascular clinics of a tertiary care hospital in Jiangsu Province, China. The research instruments included the demographic characteristics questionnaire, the Connor-Davidson Resilience Scale, the Multidimensional Scale of Perceived Social Support, and the Posttraumatic Growth Inventory. The data were collected between August 2022 and November 2022 and were analyzed using descriptive statistics and regression analyses to determine the mediating effects. Results: The level of posttraumatic growth among patients with acute coronary syndrome attending follow-up clinic visits was moderate (Mean = 60.58, SD = 14.13). Resilience had a direct and positive impact on posttraumatic growth (β = 0.361, p <0.001). Moreover, resilience fully mediated the relationship between social support and posttraumatic growth (indirect effect = 0.203, 95% CI [0.076, 0.331]; direct effect = 0.162, p = 0.101). Conclusion: Patients with acute coronary syndrome in China experience moderate posttraumatic growth after discharge. Resilience mediates the relationship between social support and posttraumatic growth. Therefore, nursing interventions focusing on promoting social support and resilience should be developed to encourage posttraumatic growth in patients with acute coronary syndrome.